Security Study and Encryption / Decryption Method - Al-Qdah, Majdi Taysir (2000)
Secure data transmission is done with a technology called encryption. Encryption software scrambles the data with a secret code so that no one can make sense of it while it's being transmitted. When the data reaches its destination, the same software unscrambles the information. Often the objectives of information security systems like encryption can only be achieved by following procedural techniques and abidance of laws. This work presents an Encryption/ Decryption System that relies on a method of data rotation and XOR operations to obtain an encryption key. It uses an encryption Master Key that is a combination of both an input password Male Key and a randomly generated number called the Female Key. The decryption procedure relies on flipping of the master key to obtain the Negative Master Key and then follows the same procedure of encryption but with a reversed Master Key. Creating the Encryption/ Decryption System was achieved by programming with Object-Oriented Pascal under Delphi 5.0 software. Testing the system was done by taking different types of files like text, image, and video and encrypting and then decrypting them using the system. The results obtained showed that in fact the system is able to perform both encryption and decryption for all sorts of files.